IMPLEMENTASI KEBIJAKAN BELA NEGARA UNTUK MEWUJUDKAN KETAHANAN NASIONAL DI WILAYAH KOMANDO DISTRIK MILITER 1309 / MANADO - Rudolf Toar Shaloom Manoppo; Agustinus ., Pati; Alfon ., Kimbal (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the implementation of State Defense policies to achieve National Resilience. This research was conducted in the area of Kodim 1309 which was carried out by the Regional Command Unit (Satkowil) namely Kodim 1309 / Manado Korem 131 / Stg Kodam XIII / Mdk in the city of Manado and its surroundings. This research was conducted from December 2019 to February 2020. This study used primary and secondary data. Primary data were obtained by observation and interview methods, while secondary data were collected using documents related to the topic of this research, particularly with regard to land defense. Interviews were conducted with 15 informants who were selected purposively. Data analysis used qualitative data analysis techniques. The results showed that, first, the communication process carried out by Kodim 1309 as the executor was carried out by building communication with stakeholders in the Kodim 1309 area, which process went well and was accepted by stakeholders and the general public. Second, the implementation of the institutional strategy of the bureaucratic structure carried out by Kodim 1309 / Manado to the Koramil in its ranks has been good through forms of supervision. Third, in the aspect of resources in implementing the national defense of the Police, Kodam 1309 uses human resources, namely army personnel and available facilities. These activities have not been maximized because there are not enough personnel so that to carry out state defense activities was limited of number and face various other activities that must also be carried out too. Fourth, the attitude of policy implementers has not shown maximum results and has not been running sustainably.